2013
DOI: 10.1111/acer.12190
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Combined Prenatal Ethanol and Prenatal Stress Exposure on Anxiety and Hippocampal-Sensitive Learning in Adult Offspring

Abstract: Background Prenatal ethanol (EtOH) and prenatal stress have both been independently shown to induce learning deficits and anxiety behavior in adult offspring. However, the interactive effects of these two developmental teratogens on behavioral outcomes have not been systematically evaluated. Methods We combined an established moderate prenatal EtOH consumption paradigm where Long-Evans rat dams voluntarily consume either a 0% or 5% EtOH solution in 0.066% saccharin water (resulting in a mean peak maternal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
(53 reference statements)
1
17
0
Order By: Relevance
“…Prenatal ethanol-exposed and prenatal stress-exposed rat offspring were generated as previously described by Staples et al (2013). Briefly, Long-Evans females and breeder males (Harlan Industries, Indianapolis, IN) were single-housed and maintained on a reverse light/dark cycle.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Prenatal ethanol-exposed and prenatal stress-exposed rat offspring were generated as previously described by Staples et al (2013). Briefly, Long-Evans females and breeder males (Harlan Industries, Indianapolis, IN) were single-housed and maintained on a reverse light/dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…1), because evidence has demonstrated that developing rodent fetuses are only susceptible to stress during the third week of gestation (Diaz, Brown, & Seckl, 1998). This paradigm has been shown to elevate maternal serum corticosterone levels 3-fold over non-stressed controls, and the rat dams do not acclimate to this stressor with repeated TMT exposure episodes (Staples et al, 2013). Additionally, this prenatal stress paradigm does not elicit significant growth deficits in the offspring, as noted in Staples et al (2013), thereby reducing the number of potential confounding factors.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations